FACTORS AFFECTING FINANCIAL DISTRESS IN NON-CYCLICAL CONSUMER COMPANIES LISTED ON IDX - Estefany, Marcelina; Salim, Susanto (International Journal of Application on Economics and Business, 2024)
This study empirically tests the influence of profitability, leverage, firm size, and corporate social responsibility (CSR) on financial distress. The study was conducted on consumer non-cyclical companies listed on the IDX during the 2020-2022 period. This study uses quantitative data obtained from financial reports, annual reports, and sustainability reports published by companies. The amount of data studied was 111 observations, which met the criteria as research samples based on the purposive sampling technique. The data was processed using the IBM SPSS version 25 program. This research shows that profitability has a significant positive effect on financial distress, while leverage significantly negatively affects financial distress. Meanwhile, firm size and CSR do not have a significant influence on financial distress.